2014
DOI: 10.1073/pnas.1324050111
|View full text |Cite
|
Sign up to set email alerts
|

Large, stratified, and mechanically functional human cartilage grown in vitro by mesenchymal condensation

Abstract: The efforts to grow mechanically functional cartilage from human mesenchymal stem cells have not been successful. We report that clinically sized pieces of human cartilage with physiologic stratification and biomechanics can be grown in vitro by recapitulating some aspects of the developmental process of mesenchymal condensation. By exposure to transforming growth factor-β, mesenchymal stem cells were induced to condense into cellular bodies, undergo chondrogenic differentiation, and form cartilagenous tissue,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
191
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(200 citation statements)
references
References 44 publications
9
191
0
Order By: Relevance
“…The stratification was evidenced by superficialzone expression of lubricin and deep-zone expression of osteopontin. We previously showed that self-assembling MSCs formed cartilage with a superficial lubricin lining after 5 wk of chondrogenic induction (10). In the present study, zonal lubricin expression was observed after implantation.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…The stratification was evidenced by superficialzone expression of lubricin and deep-zone expression of osteopontin. We previously showed that self-assembling MSCs formed cartilage with a superficial lubricin lining after 5 wk of chondrogenic induction (10). In the present study, zonal lubricin expression was observed after implantation.…”
Section: Discussionsupporting
confidence: 68%
“…Mesenchymal condensation has been adapted into selfassembly methods to enhance cartilage formation in vitro (10,11). TGF-β and thyroxine, potent effectors of cartilage maintenance and chondrocyte terminal differentiation, have been used in chondrogenic and hypertrophic induction regimens to guide MSC differentiation (4,14,(17)(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Timing may play a critical role in the success of tissue fusion13 as well as development of tissue‐specific phenotypes. As a result, cartilage and prevascular rings were cultured individually for varying time periods prior to stacking them for fusion into a composite tube to determine the impact of timing of fusion on resultant tissue structure and differentiation.…”
Section: Resultsmentioning
confidence: 99%